(untitled) (Academicia Globe: Inderscience Research, 2023)
Failure to thrive is the term used to describe the condition in which a young child fails to gain weight satisfactorily. Common reasons for such poor weight gain are parental neglect or lack of food. On the other hand, a large number of important gastrointestinal disorders may be responsible, including those associated with vomiting, such as food intolerance or obstruction of the upper bowel by pyloric stenosis; disorders of digestion and absorption, including celiac disease and cystic fibrosis; and bowel infections. Amniotic band syndrome (ABS) is a set of congenital malformations attributed to amniotic bands that entangle fetal parts during intrauterine life, which results in a broad spectrum of anatomic disturbances - ranging from minor constriction rings and lymphedema of the digits to complex, bizarre multiple congenital anomalies incompatible with life.